Optimal Unit Commitment for Minimizing Total Operating Cost using Ant Lion Optimizer - Yasin Z.M.; Sam'On I.N.; Salim N.A.; Ab Aziz N.F.; Zakaria Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Operating costs; Scheduling; Computation time; Generation scheduling; Global optimum solutions; Global solutions; Hunting behavior; Number of iterations; Reserve requirements; System constraints; Dynamic programming